An Application Of Guided Inquiry Method And Simple Media To Improve The Students’ Learning Interest And Achievement Of Math On Addition And Subtracttion Of Three Numbers For Third Graders Of Sd Negeri 2 Pagedangan - Suratmi Suratmi (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2014)
The study was aimed at improving the students’ learning interest and achievement of math on topic of addition and subtraction of three numbers though a work group as the technique to improve the learning process. It applied a classroom action research conducted following the principles of Kemmis S, C Taggart R (1988) covering planning, acting, oberserving, and reflecting or evaluating. These stages were done repeatedly and made into cycles. This was done by collaborating with the peers as observer, supervisor and the principal of the elementary school. Based on the analysis, it can concluded that (1) the students’ interest in attending the learning is better than the coventional method, by applying the guided inquiry and the simple media, (2) the students’ learning achievement also improves, by applying the method and the simple media. This can be seen from the increase of students’ learning interest from the cycle I. It was 62% and their learning mastery was 63,38% , with an average score of 70,07. At the end of the Cycle II, their learning interest improved to 82,4%. Their learning mastery was 88,46% and their average score was 78,26. Based on the findings, it can be concluded that the learning of math on addition and subtraction using guided inquiry method can be successfully applied in a classroom action research